VisualLISA: a visual interface for an attribute grammar based compiler-compiler - Pereira, Maria João (2008)
The research work that we discuss in this position paper, is concerned with the implementation of a visual front-end for LISA tool in order to make easier and more attractive the work of writing an attribute grammar for a new language. LISA (Language Implementation System based on Attribute grammars) is a compiler-compiler, or a system that generates automatically a compiler/interpreter from a formal language specification based on attribute grammars. The main idea is to design a visual language to draw derivation rules in conjunction with the associated semantic rules and to develop a visual compiler to transform that graphical representation into LISA notation.